Arch fingerprints, hypotonia, and areflexia associated with X linked mental retardation. Issue 6 (June 1997) - Stevenson, R E; Häne, B; Arena, J F; May, M; Lawrence, L; Lubs, H A; Schwartz, C E
Abstract : A syndrome with distinctive facies, poor muscle tone, absent deep tendon reflexes, tapered fingers, excessive fingerprint arches, genu valgum and mild-moderate mental retardation has occurred in four males in two generations of a white family of European ancestry. The facies are characterised by square configuration, tented upper lip, and thickening of the helices, upper eyelids, and alae nasi. At birth and at maturity, growth (head circumference, height, weight) of affected males is comparable to or greater than unaffected male sibs. Moderate impairment of cognitive function was documented (IQ scores between 40-51). Carriers show no heterozygote manifestations. This X linked condition appears to be different from other syndromes with mental retardation, although there are certain similarities with the alpha thalassaemia-mental retardation syndrome (ATR-X). Linkage analysis found tight linkage to DXS1166 and DXS995 in Xq13 and Xq21 respectively.